The influence of host genotype and gut microbial interactions on feed efficiency traits in pigs - Lu, Zhuoda; Zhang, Tao; Zhao, Yunxiang; Pang, Yanqin; Guo, Meng; Zhu, Xiaoping; Li, Ying; Li, Zhili (Frontiers in Microbiology, 2024)
Feed efficiency and growth performance are economically important traits in pigs. Precious studies have been revealed that both genetics and gut microbes could influence host phenotypes, however, the mechanisms by which they affect pig growth and feed efficiency remain poorly understood. In this study, 361 crossbred Duroc × (Landrace × Yorkshire) commercial pigs were genotyped using GeneSeek Porcine SNP50K BeadChip, and the microbiotas from fecal samples were acquired using microbial 16S rRNA gene sequencing technology to investigate the impact of host genetics and gut microorganisms on growth and feed efficiency. The results showed that the heritability and enterobacterial force ranged from 0.27 to 0.46 and 0 to 0.03, respectively. Genome-wide association studies (GWAS) identified seven significant SNPs to be associated with growth and feed efficiency, and several genes, including AIF1L, ASS1, and QRFP were highlighted as candidates for the analyzed traits. Additionally, microbiome-genome-wide association studies GWAS revealed potential links between CCAR2, EGR3, GSTM3, and GPR61 genes and the abundance of microorganisms, such as Trueperella, Victivallis, and Erysipelatoclostridium. In addition, six microbial genera linked to growth and feed efficiency were identified as follows Lachnospiraceae_UCG-005, Prevotellaceae_UCG-003, Prevotellaceae_NK3B31_group, Prevotella_1, Prevotella_9, and Veillonella. Our findings provide novel insights into the factors influencing host phenotypic complexity and identify potential microbial targets for enhancing pig feed efficiency through selective breeding. This could aid in the development of strategies to manipulate the gut microbiota to optimize growth rates and feed efficiency in pig breeding.